BIOCHEMICAL AND MOLECULAR GENETIC ANALYSIS OF POMEGRANATE (Punica granatum L.) USING HYPERVARIABLE AND CHLOROPLAST SSR MARKERS - Ibrahim, Hedi; Hama-Ali, Emad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Pomegranate is a self-pollinated species crop, and its improvement programmes depend on molecular genetics and phenotypic variation. However, inadequate information on genetic diversity and population structure among pomegranate genotypes from this region and the variations in phytochemicals hinder its improvement. In this study, 40 pomegranate samples were chosen from 11 locations to represent the genetic spectrum from the Halabja Province. The pomegranate samples were tested using 23 Hypervariable SSRs (HvSSRT) and 19 newly developed Chloroplast SSRs (cpSSR) markers. The highest values of pH (4.40), TSS (16.774 °Brix), density (1066.5 kg/m3), glucose (72.408 mg/ml), fructose (60.071 mg/ml), cyanidin-3-glucoside (71.984 mg/L), and cyanidin-3, 5-diglucoside (155.701 mg/L) were recorded among the pomegranate samples. SSR markers genotyping of pomegranate samples generated 114 alleles, and the MAF, Shannon’s information index (I), and Nei’s gene diversity for HVSSRTs were 0.570, 0.915, and 0.537, and for cpSSRs 0.618, 0.668, and 0.460. The polymorphic information content ranged from 0.129 to 0.723, with an average of 0.467 for HVSSRTs and 0.360 for cpSSRs. Finally, high levels of genetic diversity (66%) were recorded among individuals within populations, suggesting that the Halabja pomegranates are diverse.